(untitled) (Al-Aasar, 2025)
Alphabets of any language are representatives of different sounds. These are known as visible signs and symbols of a language. The structure of a word depends on these alphabetic letters. If these letters of a word are not selected in accordance with rules of a specific language then irregularity and chaos prevails, it affects the validity, effectiveness, charm and beauty of any script and language. Importance, usefulness and scope of a script of any language correct dictation. The rules of Urdu dictation should be followed at any cost for the bright future of Urdu language and literature. In this research article an effort has been made to indicate the importance of correct and valid dictation for Urdu. So that it may compete with challenges of modern linguistic world of this era.